(untitled) (Kinesiology, 2019)
The objectives of the present study were: (i) to analyse anthropometric parameters, physical fitness, and throwing speed in men elite youth handball players of different ages; and (ii) to develop a multivariate model that explains the throwing speed. Fifty-three men handball players (17.99±1.68 years in age), components of the [deleted for blinding purposes] national teams, participated in the study. The participants were classified into the under-21 National Team (n=12), under-19 National Team (n=17), and under-17 National Team (n=24). All were evaluated by basic anthropometry (height, weight, body mass index), physical fitness tests (counter movement jump, medicine ball throw, hand dynamometry, 10 m and 30 m sprint, yo-yo IR2 test) and handball throwing speed (from 7 m standing, and from 9 m after three steps and after three steps and a jump). A one-way analysis of variance with a Bonferroni post hoc test was used to establish the differences between teams. Multiple linear regression was used to predict the speed of each of the three throws for each of the three teams. There were no differences between the U21 and U19 teams except for the medicine ball throw, but the U19 team obtained better results than the U17 team in almost all variables. Throwing speed was predicted (between 22% and 70%) with only one or two physical fitness variables in each model, with medicine ball throw (four models), CMJ (two models), and 10 m sprint (two models) being the variables that were most selected.